In vivo toxicity and biodegradation studies in mimicked biological media of bare and functionalised haematite nanoparticles. (17th November 2021) - Akhtar, Kanwal; Shad, Naveed Akhtar; Sajid, Muhammad Munir; Javed, Yasir; Muhammad, Faqir; Akhtar, Bushra; Irfan Hussain, M.; Sharif, Ali; Abbas, Wasim; Munawar, Anam
ABSTRACT: Bare and functionalised haematite nanoparticles (NPs) are synthesised through the co-precipitation method and characterised using XRD, SEM, TEM, EDX, FTIR, and VSM. XRD confirmed the rhombohedral-based hexagonal structure of Fe2 O3, while, TEM and SEM showed the formation of lamellar-shaped NPs with the grain size varied from 22 to 80 nm. VSM presented soft ferromagnetic behaviour. From in vivo evaluations, changes in serum levels are analysed at different days of study after administration of bare and coated NPs through the intraperitoneal route of administration in albino rats. Toxicity parameters revealed a transient increase at day 1 but a gradual decrease thereafter. For biodegradation studies, NPs exposure in lysosomal-like medium showed insignificant changes in the absorbance spectrum for a short interval of time, however, dynamical degradation effects were observed on Day 8. Apoferritin studies disclose the growth of absorbance near 260 nm, which reveals progressive and partially filled proteins with iron ions. GRAPHICAL ABSTRACT: UF0001